Phenotypic and molecular identification of a novel thermophilic Anoxybacillus species: a lipase-producing bacterium isolated from a Malaysian hotspring. - Olusesan, Akanbi Taiwo; Kamaruzaman, Liana Azura; Abu Bakar, Fatimah; N., Sheikh Abdul Hamid; Radu, Son; Saari, Nazamid (Springer Verlag, 2009)
Eleven lipase-producing thermophilic bacteria strains were recently isolated from Kuala Woh Hot Spring, in Peninsular Malaysia. These strains have been qualitatively screened using Rhodamine B-olive oil plate agar. All strains showed lipase activity in the range of 0.56–2.62 U/ml. Their thermostabilities were then determined by incubation at 80°C for 30 min. Results showed that strain KW 6 and KW 12 produced relatively thermostable lipases, which retained 62 and 54% of their original activity, respectively. They were identified based on their morphological characteristics, biochemical tests and the Biolog system. Strain KW 12 showed exceptionally unique characteristics (over KW 6) being able to grow in a broad range of pH and temperature. It was further identified using 16S rRNA partial sequence analysis and the result of 16S rRNA partial sequence analysis identified KW 12 as Anoxybacillus kamchatkensis.